3D Viscoelastic Simulation of Jetting in Injection Molding. (8th February 2019) - Zhang, Shixun; Hua, Shaozhen; Cao, Wei; Min, Zhiyu; Liu, Yongzhi; Wang, Yaming; Shen, Changyu
Abstract : A three‐dimensional model and algorithm were proposed to simulate the jetting phenomenon in injection molding. The Giesekus model was employed to describe the viscoelastic behavior of the incompressible, non‐isothermal polymer flow, and the volume of filling method was used to track the jetting free surface and advancing melt front. The governing and constitutive equations were discretized by finite volume method. To improve the precision and stability of the numerical method, a modified pressure implicit with splitting of operator algorithm was proposed to solve the pseudo Navier–Stokes problem, and an iterative scheme was constructed to determine the solution of the coupled nonlinear equations. Numerical results showed this method successfully predicted the snake‐like flow in thin‐wall cavities and buckling flow in thick‐wall cavities. The viscoelastic characteristics of polymer influenced the reptile swing frequency and amplitude. Finally, a suitable nonlinear parameter in the Giesekus model improved the precision of simulation. POLYM. ENG. SCI., 59:E397–E405, 2019. © 2019 Society of Plastics Engineers